The relationship between outdoor games and digital game addiction - Boğa Baran, Ebru; Sağlam, Mehmet (Journal of Dependence, 2023)
Objective: The aim of this study was to examine the relationship between Digital Game Addiction and Outdoor Games. Method: The study was carried out by quantitative method.. As a data collection tool in research; The Demographic Information Form prepared by the researcher, Questionnaire Form prepared for children and their families by taking expert opinion, and the “Digital Game Addiction Scale for Children” were used. Results: With digital game addiction; there was no significant difference between children’s thoughts of playing outside, duration of playing, playing outside and playing digital games at home; it was determined that there is a significant difference between the places where games are played outside and the relationships with friends. Conclusion: Although there is unlimited internet at home, children like to play outside, and children who do not have their own computer and smart phone at home prefer to play outside.